2018
DOI: 10.1016/j.jsat.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Training community-based treatment providers to implement contingency management for opioid addiction: Time to and frequency of adoption

Abstract: Contingency management (CM) is a well-established treatment for opioid use, yet its adoption remains low in community clinics. This manuscript presents a secondary analysis of a study comparing a comprehensive implementation strategy (Science to Service Laboratory; SSL) to didactic training-as-usual (TAU) as a means of implementing CM across a multi-site opioid use disorder program. Hypotheses predicted that providers who received the SSL implementation strategy would 1) adopt CM faster and 2) deliver CM more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 50 publications
0
48
0
1
Order By: Relevance
“…Nine (45%) of included studies were randomised controlled trials [59,61,62,[65][66][67][68][69], eight (40%) were randomised trials [39,42,43,50,54,60,70,71](one of which was a subject-by-trial split plot design with repeated measures, [50]), one was a cluster randomised trial [45], one was an interrupted time series design [55], and one was a controlled before-and-after study [47]. Studies varied in terms of the number of participants, the length of follow-up period, the number of addiction services clinicians were sourced from, and the levels of intervention in the approach.…”
Section: Study Designsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine (45%) of included studies were randomised controlled trials [59,61,62,[65][66][67][68][69], eight (40%) were randomised trials [39,42,43,50,54,60,70,71](one of which was a subject-by-trial split plot design with repeated measures, [50]), one was a cluster randomised trial [45], one was an interrupted time series design [55], and one was a controlled before-and-after study [47]. Studies varied in terms of the number of participants, the length of follow-up period, the number of addiction services clinicians were sourced from, and the levels of intervention in the approach.…”
Section: Study Designsmentioning
confidence: 99%
“…manuals and seminars) and active (e.g. supervision, workshops and champions) approaches to training [47,59,62,65,66,68,71], while 20% (n = 4) focused on discrete strategies (e.g. supervision [61], financial incentives [45], booster sessions [50], and workshop only [46]).…”
Section: Types Of Strategies Evaluatedmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found that the SSL outperformed didactic training-as-usual (without performance feedback or ongoing facilitation) for enhancing CM implementation speci cally in OTPs. SSL resulted in both higher adoption and faster implementation of CM when compared to didactic training-as-usual, providing additional evidence for the utility of the performance feedback and ongoing facilitation strategies [19,20].…”
Section: Introductionmentioning
confidence: 84%